Overview of Research on Vanadium-Quercetin Complexes with a Historical Outline - Agnieszka Ścibior (MDPI AG, 2022)
The present review was conducted to gather the available literature on some issues related to vanadium-quercetin (V-QUE) complexes. It was aimed at collecting data from in vitro and in vivo studies on the biological activity, behavior, antioxidant properties, and radical scavenging power of V-QUE complexes. The analysis of relevant findings allowed summarizing the evidence for the antidiabetic and anticarcinogenic potential of V-QUE complexes and suggested that they could serve as pharmacological agents for diabetes and cancer. These data together with other well-documented biological properties of V and QUE (common for both), which are briefly summarized in this review as well, may lay the groundwork for new therapeutic treatments and further research on a novel class of pharmaceutical molecules with better therapeutic performance. Simultaneously, the results compiled in this report point to the need for further studies on complexation of V with flavonoids to gain further insight into their behavior, identify species responsible for their physiological activity, and fully understand their mechanism of action.